Incentivised physical activity intervention promoting daily steps among university employees in the workplace through a team-based competition - Safi, Ayazullah; Deb, Sanjoy; Kelly, Adam; Cole, Matthew; Walker, Natalie; Zariwala, Mohammed Gulrez (Frontiers in Public Health, 2024)
The benefits of walking on health and well-being is well established and regarded as the most accessible form of physical activity (PA) that most individuals can incorporate into their lives. Despite the benefits, the impact of a competitive walking intervention combined with a prize incentive in the workplace is yet to be established. The aim of this intervention was to promote PA among university employees through teams-based competition with a prize incentive targeted towards the recommended 10,000 steps per day. Methods: A total of 49 employees participated and formed eight departmental teams ranging from Senior Admin management, Educational & Social work, Nursing & Midwifery, Sport & Exercise, Health Sciences, Admin Assistant, Library, and IT to compete in a walking intervention. Each team was handed an ActiGraph wGT3X-BT from Monday to Friday to record their walking steps. steps. Post intervention participants completed an open-ended survey to provide their views about the intervention. Results: The ActiGraph findings determined that steps increased by 4799 per day from daily baseline of 5959 to 10758 throughout this intervention. The themes from qualitative data showed that the prize incentive and competitive nature of this intervention has motivated staff to walk more, changed their behaviour, enjoyed the team-based competition, and improved perceived productivity in the workplace. Discussion and conclusion: This intervention increased employees' daily steps by 4799 and met the 10,000 steps guideline. The 'Health Sciences' team recorded the highest steps 531,342 followed by the 'Education and Social Work' accumulating 498,045 steps throughout this intervention. This intervention with prize incentive demonstrated a positive impact on employees personal and work-based outcomes as well as contributed to the workplace PA, health, and wellbeing literature, and more specifically, to the scarce research focused on university settings.